Politik Etnosentris Semu Dalam Kasus Upaya Pemekaran Provinsi (Studi Pada Gerakan Pemekaran Provinsi Cirebon) - Ficky Utomo; Julian Aldrin Pasha (Empower : Jurnal Pengembangan Masyarakat Islam, 2020)
This study discusses about the ethnocentric based political movements that are false (pseudo- ethnocentric politics) in the case of deadlock effort for Cirebon Provinces segregation. This study uses the theory of governability, Theory of Social Movements, Theory of ethnocentrism, and the Theory of Rent-Seeking in dissecting the issue of the proposed research regarding the causes of ontological substance of the Cirebon Province segregation movement, how the movement of the expansion is done, the goal of some parties spreading issues about ethnocentric in the period of Cirebon Province divergence movement, and finally as a tool for analysis to uncover the reasons substantially deadlock Keraton Cirebon Elit effort with the P3C Organization in Cirebon and its Provinces movement determinant implications after the deadlock occurred. By using qualitative methods of the literature and collected data through in-depth interviews. Researchers have argued that the conditions of management of the West Java Provincial Government in the category of un-governability was the cause of the ontological substance of Cirebon Province segregation movement. That the derivation is the rise of forms of movement by the elites and activists Provinces Cirebon. The researchers also found, the issue of ethnocentrism used as a propaganda tool in order to strengthen the solidity of the group. And the reason for the deadlock substantive motion Cirebon Provinces is more to the practice of rent-seeking among the position holders involved (central and regional). In this study were also presented regarding the emergence of the idea for transfer the Capitalcity to Cirebon and Majalengka and the movement for divergence the district of Indramayu and Cirebon as a result of the deadlock implikatif (discontinuities) of Cirebon Province segregation movement.